Trends in spatiotemporal distribution of pulmonary tuberculosis morbidity and mortality in China: 2004 - 2018 - Nan CHU; Qian-qian GAO; Cheng-chao ZHOU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore spatiotemporal distribution of pulmonary tuberculosis (TB) morbidity and mortality and their changing trend in China from 2004 to 2018 and to provide evidence for conducting relevant studies and developing strategies on TB prevention and treatment. MethodsNationwide data of 2004 - 2018 on TB surveillance were collected and demographic data of the same period were extracted from China Statistical Yearbook. The 15-year period was divided into three stages. The spatial characteristics of TB morbidity was analyzed with Excel 2010 software and Stata 14.0 was used to analyze spatial autocorrelation. Results During the period, totally 14 816 329 TB incidents were reported in China, with an average incidence rate of 73.9029/100 000 and an average annual reported mortality of 0.2114/100 000. Spatial autocor-relation of TB morbidity in different regions was observed. ConclusionDuring 2004 - 2018 in China, the incidence rate of pulmonary tuberculosis was decreasing generally and there were aggregations and significant regional differences in TB morbidity.